Taxonomy, biostratigraphy and phylogenetic affinities of Eocene Astrorotalia, Igorina, Planorotalites, and problematica (Praemurica? lozanoi) - W. A. Berggren; D. K. Olsson; I. Premoli Silva (Cushman Foundation for Foraminiferal Research, 2006)
In this chapter we treat the taxonomy, stratigraphic distribution and phylogenetic affinities of Eocene muricate, nonspinose species of the genera Astrorotalia, Igorina and Planorotalites. Igorina had an early mid-Paleocene praemuricate ancestry and evolved at about the same time (Zone P3a; early Selandian) as the earliest morozovellids (praeangulata,angulata); the genus became extinct in Zone E9 (early middle Eocene). Planorotalites pseudoscitulus evolved in the latest Paleocene (Zone P5) from a possible morozovellid (? Morozovella occlusa) ancestry. It evolved into the stellate, peripherally carinate, monospecific, stratigraphically restricted species A. palmerae in Zone E7 (upper lower Eocene). Seven species are recognized and discussed, namely Igorina anapetes (Blow), Igorina broedermanni (Cushman and Bermúdez), Igorina lodoensis (Mallory), Igorina tadjikistanensis (Bykova), Planorotalites capdevilensis (Cushman and Bermúdez), Planorotalites pseudoscitula (Glaessner), and Astrorotalia palmerae (Cushman and Bermúdez). Planorotalites renzi (Bolli) is confirmed as a junior synonym of P. capdevilensis. Our attempts to find an appropriate generic home for ‘Globigerina lozanoi Colom’ have been unsuccessful for reasons explained below. We assign lozanoi provisionally to Praemurica.